Here is a question where we are asked to make a the subject of the formula V=u+at.

“This question is derived from the first equation of motion V=u+at”.

If you are unfamiliar with the topic subject of the formula, this question will serve as an example.

This question might also be given this way.

Rearrange v=u+at to make a the subject

We won’t cover everything about the main topic, but this question will be treated ideally.

## Make a The Subject Of The Formula V=u+at

Let me give you this hint. Whenever you are dealing with fractions, the first thing you do is to find the LCM.

If the question has plus (+) or minus (-), add the values or subtract them if they are like terms.

If there is an equal sign, collect like terms and change the sign before the number or variable.

Take, for instance, we are to make u the subject of the formula in this question

**v=u+at**

All you need to do is move the “**at**” to the other side. While moving this, change the sign i.e. from plus (+) to minus (-).

So we now have **v-at=u**

If two alphabets or one alphabet and number are together always apply division.

For example, 2s=10 make s the subject of the formula. What you have to do here is to divide both sides with the co-efficient of s, which is 2.

2s/2 = 10/2

S=5.

Back to our Make a the subject of the formula v=u+at

**Step 1:**move u to the other side. v-u=at**Step 2:**Divide both sides by the co-efficient of a v-u/t =at/t- Finally, we arrive at
**a=v-u/t**

## The subject of the formula Questions

You can also try to solve these questions on the formula’s subject change below.

- Make h the subject of the formula
**u=h+vt**

- Make n the subject of the formula
**at=n+z**

Kindly drop your answer in the comment box below.

Sam is a brilliant young Nigerian biochemistry student and an aspiring entrepreneur. Despite facing many challenges, he has never lost his passion for learning and drive to make a difference in the world. Read more about him here.

Just wanted to say great blog. Keep up the good work!

Thanks

Well done sir thanks for elightening us sir we appreciate you.

Thanks sir

making h the subject of the formula

U=h+vt

we move vt to the other side den we have

u-vt=h

Wow